2000
DOI: 10.1046/j.1523-1755.2000.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide modulates expression of matrix metalloproteinase-9 in rat mesangial cells

Abstract: We conclude that NO modulates cytokine-mediated expression of MMP-9 and TIMP-1 in rat MCs in culture. Our results provide evidence that NO-mediated attenuation of MMP-9 gelatinolytic activity is primarily due to a reduced expression of MMP-9 mRNA, and not the result of direct inhibition of enzymatic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(140 citation statements)
references
References 25 publications
(5 reference statements)
7
131
2
Order By: Relevance
“…Moreover, we considered the activity and expression of two proteins (iNOS and MMP2) as playing an important role in nephrotoxicity (Eberhardt et al 2000;Khanna et al 2002;Rezzani et al 2003;Buffoli et al 2005) and found an induction of these proteins after CsA treatment. Of note, it seems that these data underlie an increase of these proteins in apical membrane of Henle loops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we considered the activity and expression of two proteins (iNOS and MMP2) as playing an important role in nephrotoxicity (Eberhardt et al 2000;Khanna et al 2002;Rezzani et al 2003;Buffoli et al 2005) and found an induction of these proteins after CsA treatment. Of note, it seems that these data underlie an increase of these proteins in apical membrane of Henle loops.…”
Section: Discussionmentioning
confidence: 99%
“…To help to address these questions we studied the activity and expression of two proteins responsible for CsA nephrotoxicity in adult rats: inducible nitric oxide synthase (iNOS, NOS2) (Rezzani et al 2003;Buffoli et al 2005) and matrix metalloproteinase-2 (MMP2) (Eberhardt et al 2000;Khanna et al 2002).…”
mentioning
confidence: 99%
“…Assessment of gelatinolytic MMP-9 content of proteins from cellular supernatants was performed as described previously [22]. Proteins with gelatinolytic content were visualized as areas of lytic activity on an otherwise blue gel [23].…”
Section: Sds-page Zymographymentioning
confidence: 99%
“…cDNA inserts for rat MMP-9 and TIMP-1 were generated as described previously [22]. A cDNA insert from mouse 18S rRNA was from Ambion (Austin, TX, USA).…”
Section: Cdna Clones and Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation